IMPLEMENTASI PERATURAN DAERAH KOTA PALEMBANG NOMOR 12 TAHUN 2013 TENTANG PEMBINAAN ANAK JALANAN, GELANDANGAN DAN PENGEMIS - Aspani, Budi; Yusmanda, Riza (Faculty of Law, University of Palembang, 2020)
The problem of street children is a complex social problem related to other social problems such as poverty, neglect, victims of violence, due to natural disasters and so on. In the last decade, the problem of street children, homeless people and beggars has become one of the crucial problems both in terms of the complexity of the problem and the increasing quantity of neglected children. This study aims to look at how the Implementation of Palembang City Regulation Number 12 of 2013 concerning the Development of Street Children, Homeless and Beggars and determine the factors that are driving and inhibiting the Implementation of this Regional Regulation. This research is a qualitative descriptive study that is a study that is describing how the implementation and conditions in the field and data collection techniques in the form of field studies by conducting direct interviews with relevant parties. The results showed that the Implementation of Palembang City Regulation Number 12 of 2013 was good enough, it can be seen from the decreasing number of street children, homeless people and beggars in Palembang City. In addition, it is expected that a review of this regional regulation is expected to be needed, this is in line with conditions and conditions in the environment that may no longer be the same so that this Regional Regulation needs to be revised.